2021
DOI: 10.1080/23279095.2021.1900188
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of limb apraxia in patients following stroke: A systematic review

Abstract: Apraxia is widely used to describe one of the more disabling deficits following left strokes. The role of rehabilitation in treating apraxic stroke patients remains unclear. This systematic review was conducted to study the impacts of various rehabilitation interventions on the limb apraxia post-stroke. PubMed, SCOPUS, PEDro, CINAHL, MEDLINE, REHABDATA, and Web of Science were searched for the experimental studies that investigated the effects of the rehabilitation interventions on apraxia in patients with str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Despite the prevalence of limb apraxia and the known impact of apraxia on function only one trial conducted in the past decade was identified. There is clearly a need for more research in this area and previous systematic reviews (Alashram et al, 2021; Lindsten-McQueen et al, 2014; Worthington, 2016) echo the need for further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the prevalence of limb apraxia and the known impact of apraxia on function only one trial conducted in the past decade was identified. There is clearly a need for more research in this area and previous systematic reviews (Alashram et al, 2021; Lindsten-McQueen et al, 2014; Worthington, 2016) echo the need for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the database searches for this review were concluded in 2012. Alashram et al (2021) published a systematic review concluding that the effects of strategy training and gesture training on apraxia post-stroke are promising. This review also has some limitations, it was not prospectively registered, it includes studies without control groups, PEDro was utilised to assess the methodological quality of randomised controlled trials (RCTs) and non-RCTs included in the review, a meta-analysis was not conducted, and the search concluded in September 2020.…”
Section: Introductionmentioning
confidence: 99%
“…13,19,20 A equipe de fisioterapia, juntamente com outros profissionais de saúde, desempenha um papel fundamental na avaliação e na implementação dessas intervenções, garantindo uma abordagem abrangente e personalizada para a reabilitação dos pacientes. 21 Concluída a avaliação do paciente, foi observado relato de dor na região do ombro direito, classificada com uma intensidade de grau 7 na escala de dor. O paciente exibia uma marcha hemiplégica, conhecida também por marcha ceifante, caracterizada por arrastar os pés, necessitando de assistência durante a deambulação.…”
Section: Relatounclassified
“…The inability to successfully complete ADLs can significantly impact upon the stroke survivor's ability to live independently as well as reintegrate back into the community and is influenced by the presence of physical or cognitive impairments. Despite the importance of being able to successfully complete ADLs, research investigating ADL performance following stroke is limited [10][11][12] and it is currently unknown which is the most effective way to target the rehabilitation of ADLs in stroke survivors although recent randomised-control trials for upper limb apraxia have shown promise [13]. Rehabilitation of impairments in ADLs associated with apraxia and action disorganization syndrome (AADS) after stroke is the focus of the present paper.…”
Section: Introductionmentioning
confidence: 99%